The legitimacy of the common security and defence policy of the European Union: a critical discourse analysis of the EU's normative justification as a crisis management actor - Ribeiro, I. M. (2019)
Legitimacy is mostly how institutions and polities ensure compliance / endorsement in the absence of coercion. Looking at the European Union’s actorness in crisis management, since the creation of the CFSP and of the ESDP in the 1990s until the 2016 Global Strategy, we analyse how it seeks to legitimate its identity and actions by justifying them normatively through discourse. We highlight the importance of normative justification in ensuring actorness legitimacy, as not a lot of attention is paid to the EU's discursive ability to convince other actors in the international system of its appropriateness to engage in external action, especially when strong normative components are involved. The area of crisis management is marked by its emergency and crisis nature and deployment on a case-by-case basis, unlike most external policies, so the EU’s normative justification narratives focus on its own potential role, identity, and value-added, rather than on countries that might receive this help. Thus, we focus on how the EU convinces others and itself (including the governments and wider public in its Member States) to validate and endorse it, rather than on the receiving end of the policy. We use critical discourse analysis (CDA) embedded in post-structuralism due to their focus on deconstruction and critique of asymmetric power relations, their effort to "denaturalise" meta-narratives that shape the social world, and due to the importance of language and discourse for the legitimation of organised power relations. The identified narratives reveal an asymmetry between the EU and its interlocutors: the EU assumes that others want to emulate its standards, brands itself as an ideal model, and places itself at a superior level. Thus, by attempting to make others "normal" and "adequate" by organising and modernising them according to the standards that the EU considers ideal or universal, the EU assumes a "civilising" attitude that goes beyond crisis management.